Visual and refractive outcomes and glistenings occurrence after implantation of 2 hydrophobic acrylic aspheric monofocal IOLs. Issue 7 (July 2020) - Stanojcic, Nick; O'Brart, David; Hull, Christopher; Wagh, Vijay; Azan, Elodie; Bhogal, Mani; Robbie, Scott; Li, Ji-Peng Olivia
Abstract : This 12-month randomized controlled trial found no difference in visual outcomes between Clareon and PCB00 IOLs in terms of visual outcomes, glistenings, perioperative or postoperative complications, or patient-reported outcome measures. Abstract : Purpose: To compare the Clareon IOL with the Tecnis PCB00 IOL in terms of visual performance, refractive outcomes, glistenings occurrence, and quality-of-life outcomes. Setting: Guy's and St Thomas' NHS Foundation Trust, London, United Kingdom. Design: Single-center, single-masked, prospective, randomized controlled trial. Methods: One hundred thirty-nine patients with bilateral cataracts were randomized to receive the Clareon (C IOL) or Tecnis (T IOL) IOL. Visual acuity, refraction, central corneal thickness (CCT), endothelial cell loss, contrast sensitivity, mesopic gap acuity, evaluation of glistenings, and rates of perioperative and postoperative complications were recorded. Quality-of-life outcomes were measured with the EuroQOL-5 dimensions questionnaire and the patient-reported outcome measures (PROMs) questionnaire. Optimized A-constants were available for the T IOL but not for the C IOL. Results: Seventy-one patients (140 eyes) received the C IOLs and 68 patients (134 eyes) received the T IOLs. Data were analyzed for the first implanted eye. At 12 months, mean uncorrected distance visual acuity (logarithm of the minimum angle of resolution) was 0.02 ± 0.10 and 0.01 ± 0.08 (mean ± SD; P = .49; 95% CI, −0.02 to 0.04) in the C IOL and T IOL groups, respectively. Corrected distance visual acuity was −0.02 ± 0.09 and −0.03 ± 0.06, respectively ( P = .45; 95% CI, −0.02 to 0.04). The increase in CCT was 14 ± 19 and 16 ± 28 μm, respectively ( P = .63; 95% CI, −10.16 to 6.16). Mean absolute refraction spherical equivalent error from target refraction was 0.41 ± 0.28 for the C IOL and 0.25 ± 0.2 for the T IOL groups ( P = .002; 95% CI, 0.08 to 0.24). Glistenings were minimal (median grade 0), with no difference in grades between groups ( P = .2). PROMs improved postoperatively and were similar in both groups. Conclusions: There were no differences in visual outcomes between the Clareon IOL and Tecnis PCB00 IOL. Glistenings were rarely observed in either IOL with no difference in grades. There was no difference in perioperative or postoperative complications. Surgeon optimization of the A-constant for the Clareon IOL is recommended.